Effect of Specific Probiotic Mixture on Coronavirus (FCoV) Viral Load in 25 Naturally-Infected, Clinically Healthy, Purebred Birman Cats - Mangiaterra, Sara; Cerquetella, Matteo; Gavazza, Alessandra; Turba, Maria Elena; Berardi, Sara; Biagini, Lucia; Rossi, Giacomo (Archives of Clinical and Biomedical Research, 2024)
Feline coronavirus (FCoV) causes enteric disease in cat woFCoVde characterized by self- limiting gastroenteritis. Not understood pathogenic changes can give rise to mutants that lead to feline infectious peritonitis (FIP). Current evidence shows that probiotics increase benefits protecting from viral infection, there are no studies regarding the use of probiotics against feline coronavirus in naturally infected cats. The aim of the present study was the evaluation of the effect of specific multi-strain probiotics on FCoV viral load in 25 purebred Birman cats (14 females and 11 males), aged from 1 to 4 years, and positive for FCoV by genetic analysis on fecal sample. Two microcaps of probiotic formulation were administered to all cat once a day for 60 consecutive days. After probiotic administration, clinical conditions and FCoV viral load was assessed by RT PCR on fecal samples. Treated cats did not demonstrate noticeable side effects after probiotic administration; seventeen out of 25 cats tested negative at the end of the study. The results of the present study show the absence of fecal FCoV viral load after live probiotics supplementation.